Bayesian modelling the retreat of the Irish Sea Ice Stream. (14th February 2013) - Chiverrell, Richard C.; Thrasher, Ian M.; Thomas, Geoffrey S. P.; Lang, Andreas; Scourse, James D.; van Landeghem, Katrien J. J.; Mccarroll, Danny; Clark, Chris D.; Cofaigh, Colm Ó; Evans, David J. A.; Ballantyne, Colin K.
Abstract We present an 8000‐year history spanning 650 km of ice margin retreat for the largest marine‐terminating ice stream draining the former British–Irish Ice Sheet. Bayesian modelling of the geochronological data shows the ISIS expanded 34.0–25.3 ka, accelerating into the Celtic Sea to reach maximum limits 25.3–24.5 ka before a collapse with rapid marginal retreat to the northern Irish Sea Basin (ISB). This retreat was rapid and driven by climatic warming, sea‐level rise, mega‐tidal amplitudes and reactivation of meridional circulation in the North Atlantic. The retreat, though rapid, is uneven, with the stepped retreat pattern possibly a function of the passage of the ice stream between normal and adverse ice bed gradients and changing ice stream geometry. Initially, wide calving margins and adverse slopes encouraged rapid retreat (∼550 m a−1) that slowed (∼100 m a−1) at the topographic constriction and bathymetric high between southern Ireland and Wales before rates increased (∼200 m a−1) across adverse bed slopes and wider and deeper basin configuration in the northern ISB. These data point to the importance of the ice bed slope and lateral extent in predicting the longer‐term (>1000 a) patterns and rates of ice‐marginal retreat during phases of rapid collapse, which has implications for the modelling of projected rapid retreat of present‐day ice streams. Copyright © 2013 John Wiley & Sons, Ltd.